(untitled) (Journal of Social Sciences Review, 2024)
This research delves deeply into the origins and evolving dynamics of various regions in Pakistan, presenting a nuanced and intricate image shaped by diverse elements and social intricacies. The interplay between global developments and inherent complexities has given rise to a milieu fraught with persistent challenges. These regions, steeped in historical tribal traditions, have experienced pronounced instability, exacerbated by pivotal events such as the Soviet-Afghan War. The study systematically investigates the transformative journey of terrorism and insurgency, scrutinizing the contributing variables. The primary objective of this paper is to furnish readers with a comprehensive understanding of the factors underpinning terrorism and insurgency in Pakistan’s tribal areas. It accomplishes this by delving into historical events, cultural components, and geopolitical influences that have intricately woven the tumultuous past of the region.